Ciências, arte e paisagismo sustentável: construindo mini-jardins com os anos finais do ensino fundamental - Diogo, Tibério Sávio Forte (2024)
The dialogue between common sense knowledge and scientific knowledge is permeated by science teaching. Science teaching enables students to mediate the way they perceive the components of nature with the concepts worked on in the classroom. In this sense, to enhance this conversation between knowledge, the present work has the general objective: to analyze the contributions of an educational product, using sustainable landscaping as an element of integration between Science and Art in teaching practice. An educational product in the form of a sustainable landscaping manual was developed. The product it9s divided into two chapters entitled "Green Harmony= and <Landscapes of Hope=. In the first chapter, students will experience the concepts that will allow them to understand their artistic-landscape elements that will enable the teaching of science through art, with sustainable landscaping being the element of art-science integration. This manual is configured as an art-science didactic proposal in which the research will use a narrative of planned experiences as a means of investigating the potential of the proposal and validating how the practice took place in the teacher9s own perception. The present work finds justification in the importance of making sustainable landscaping a consistent reality in everyday school life, with this reality of art-science integration being constructed by the students themselves. Among the main results obtained, the following stand out: good applicability of the Educational Product in teams, providing synergistic learning of knowledge; express expression of doubts, conclusions and comments, which is indicative of autonomy in relation to one9s own learning. To analyze the data obtained, Bardin9s (2020) content analysis was used, building units of analysis and categories discussed based on the theoretical framework.